The coronavirus conundrum - New subvariants of SARS-CoV-2 subvariants - COVID-19 and pregnancy - Is there a bright side to the pandemic? - Romero, José Pacheco (2022)
Since the late 2020's it was anticipated that the SARS-CoV-2 coronavirus wouldstay with us indefinitely, but there was hope that we would be able to combat itat some point effectively so that it would not produce the severe illness and deaththat we were seeing at that time. The pandemic has continued with this coronaviruscontinually modifying itself to enter the human body more easily. The Omicronvariant preferentially infects the upper respiratory tract. And some of its mutationsappear to affect parts of the spike protein that bind to ACE2. One of the latestsubvariants of the variants, BA.212.1, infects more people more rapidly, althoughcases of severe infection and deaths have declined considerably. The following isa summary of what has been known in this first quarter of the year 2022 about theparticularities of the virus, how it infects and its consequences, the protection ofvaccination, what's new about the pregnant woman and her newborn, and whetherthere is any good side to the occurrence of the COVID-19 pandemic.